Technologization of managerial activity: content and purpose. (Economics and region, 2018)
It is shown that technologization of managerial activity as visible distinctive feature of enterprise managing is direct outcome of informatization and using IT in management. Notion of «technology of management» is considered. Purpose of technologies of management is shown. Groups of actions that build technology of management are suggested. There are two big groups of technologies of management considered in the article – professional technologies and technologies of human resources management. Some characteristics of technologies of management are considered. Some problematic issues in sphere of making and using technologies of management that are necessary to be solved are highlighted.
Keywords: enterprise; management; technologization; technology of management